Pengaruh motivasi muâamalat (bekerja dan berproduksi, kebutuhan sekunder, kebutuhan primer) terhadap prestasi kerja yang religius - Wibisono, Chablullah (IJTIHAD Jurnal Wacana Hukum Islam dan Kemanusiaan, 2013)
Observing the development and growth of modern markets that is not comparable to traditionalmarkets and folk market, has described the tendency of secondary needs (psychological) which aredominant, and has been proven by Consumption Patterns Survey Central Bureau of Statistics (1991-2012). The survey shows that spending to meet the secondary needs amounted to 62.56% while for theprimary requirement of 37.44%. The order to meet the secondary needs and primary needs exist in theQurâan, but all of them in order to improve the achievement of the religious (pious charity) is not tosatisfaction solely. Based on a survey of consumption patterns and theories about the need for secondaryand work performance, attractive to the research, is there a need for Secondary Effect on Achievementof the Religious? From the loading factor corfirmatory muâamallat with second order factor Analysis isas follows: secondary needs loading factor = 1.00 (significant). This figure shows that the needs of mostlarge secondary needs described by the variation of muâamallat motivation. In other words secondaryrequirement is the most powerful indicator (dominant) of muâamallat motivation (work and production,needs secondary, needs primary, work performance of religious).